지역축제의 성장단계별분석과 관리전략 : 함평나비축제와 화천산천어축제를 중심으로 - 김현욱; Kim, Hyeonwook (한국콘텐츠학회 논문지, 15(5), 2015)
The purpose of this study is to analyze the characteristics of two local festivals, already recognized as a successful regional cultural festival, over a period of time to apply the product life cycle theory. As a result of the analysis of the two festivals, in introduction stage, the festival organizers have focused mainly on settling down the festival's core programs and raising awareness on the subject of the festival for the stimulation for basic demands. Second, for maintaining increasing demands, the qualitative improvement of the core program, the development of new programs and the expansion of the programs for the visitors' convenience and safety were focused on. In addition, strategies for promoting awareness of the festival had modified the strategy to promote on the contents and programs of the festival, as well as public relations strategy, not only domestic but also the foreign countries, was established and fulfilled. Lastly, in maturity stage, to overcome declining the number of visitors and economic effect both festivals have showed providing sophisticated programs for the visitors' convenience and safety, improving service quality through the development of the existing programs, providing economic benefits such as admission cuts or giving gift certificates and expanding number of foreign visitors with strengthening the promotion that was implemented in growth stage and enhancing the better image of the festival through the social contribution. Therefore, strategies for the each stage mentioned above present the significant policy implications for festival organizers who were planning to establish a new festival or implementing a festival with experiencing the tepid growth. 본 연구는 국내에서 이미 성공적인 지역문화축제로 인정을 받은 두 개의 지역축제를 대상으로 시간의 경과에 따라 나타나는 특징들을 제품생명주기이론에 따라 구분하여 분석을 시도 하였다. 분석결과 두 축제 모두 축제의 도입기에는 축제의 핵심프로그램의 안착과 축제의 주제에 대한 인지도를 제고하는데 관심과 역량을 집중했으며, 성장기에는 인지도 향상에 따라 증가하는 수요를 유지하기 위하여 핵심프로그램들의 질적 향상, 새로운 프로그램의 개발과 보완, 방문객 편의와 안전에 대한 프로그램의 확장에 초점을 두었고 도입기에서의 인지도 제고에 대한 홍보 전략도 축제의 내용과 프로그램에 대한 홍보로 수정하였으며, 국내 뿐 아니라 외국에 대한 홍보 전략도 수립하였다. 마지막으로 성숙기에는 감소되거나 둔화되는 방문객수와 경제적 효과를 극복하기 위해 두 축제는 새로운 수요의 창출과 기존의 소비량이 늘어날 수 있도록 방문객의 편의, 안전을 위한 프로그램과 핵심프로그램의 개선과 보완을 통한 서비스질의 향상과 입장료 인하 또는 상품권의 제공과 같은 경제적 이익의 제공, 성장기에서 추진했던 외국홍보의 강화 그리고 소외계층의 참여확대를 통한 사회적 기여 이미지 제고 등의 전략적 변화를 보였다. 따라서 두 축제의 이러한 성장단계별 전략적 변화는 새로이 지역축제를 기획하거나 이미 개최중이지만 미온적 성장에 그치고 있는 지역축제들의 주체들에게 정책적 함의를 제시한다.